Analysis of Differences in Real Costs of Hospital With Ina-Cbg’s Rate on Sectio Caesarea - Alifatul Mahmudah Nuryanawati; Ni Made Sukartini; Wahyu Aditama Putra Mukti Wibawa (Airlangga Development Journal, 2026)
The purpose of this study is to analyze the causes of the difference in real hospital rates with INA-CBG's inpatient rates in cases of cesarean delivery at Dr. Soegiri Lamongan Hospital in 2022 to control cost to be effective and efficient. The method of research is descriptive with a quantitative approach. The techniques used in data collection are observation, interviews, literature studies, and documentation. This research instrument uses a data processing table. The results of research at Dr. Soegiri Lamongan Hospital showed that INA-CBG's rates were less than the real hospital rates. This shows that the difference between the real hospital rate and INA-CBG's rate is not small so that it has the potential to be detrimental to the hospital , therefore the hospital must be able to Controlling costs by implementing service standardization so that hospital costs can be reduced with standards to be more efficient and can reduce variations in Expected services can easily predict costs and more standardized services. Cost control efforts by implementing service standardization by implementing periodic Monev with related parties on inpatient services for gastrointestinal childbirth cases caesarea at RSUD dr. Soegiri Lamongan. and the provision of rewards and punishments for the implementation of health service standardization.